Carbohydrate antigen 19-9 in saliva: possible preoperative marker of malignancy in parotid tumors - Dyckhoff, Gerhard; Warta, Rolf; Gonnermann, Achim; Plinkert, Peter K.; Flechtenmacher, Christa; Volkmann, Martin (Otolaryngology - head and neck surgery, 2011)
Objective. Facial nerve preservation and oncological safety are crucial in surgery of parotid tumors. An unexpected histopathologic diagnosis of a malignant parotid tumor, however, may unfavorably require a second, more radical surgery. The aim of this study was to find out whether the assessment of serological tumor markers in parotid saliva might have some diagnostic significance in the preoperative differentiation between benign and malignant parotid lesions., Study Design, Setting, Patients, and Methods. In a prospective pilot study performed at a university medical center in 28 patients with a unilateral parotid tumor, 7 serological tumor markers established in the clinical routine were quantitatively assessed in parotid saliva collected simultaneously on both sides after stimulation. The results were correlated with the histopathological diagnosis., Results. Of the 4 investigated tumors that were malignant neoplasms, 3 had a sufficient quantity of saliva available for tumor marker measurements. Carbohydrate antigen 19-9 (CA 19-9) consistently revealed high levels compared with the unaffected side in all malignant tumors, thus allowing malignant tumors to be differentiated from benign lesions., Conclusion. The results of this pilot study are encouraging, showing that preoperative tumor marker investigation in saliva from parotid glands is feasible and merits further investigation. CA 19-9 might be a valuable new diagnostic tool in the preoperative differentiation between malignant and benign parotid tumors and should be investigated in a larger number of patients.